2014
DOI: 10.1371/journal.pone.0089873
|View full text |Cite|
|
Sign up to set email alerts
|

Population Explosion in the Yellow-Spined Bamboo Locust Ceracris kiangsu and Inferences for the Impact of Human Activity

Abstract: Geographic distance and geographical barriers likely play a considerable role in structuring genetic variation in species, although some migratory species may have less phylogeographic structure on a smaller spatial scale. Here, genetic diversity and the phylogenetic structure among geographical populations of the yellow-spined bamboo locust, Ceracris kiangsu, were examined with 16S rDNA and amplified fragment length polymorphisms (AFLPs). In this study, no conspicuous phylogeographical structure was discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 94 publications
1
13
0
Order By: Relevance
“…One distinct characteristic of the species is its greater flight ability, presumably leading to frequent gene flows between populations. Fan et al previously reported that this species has low levels of genetic structure and relatively high gene flow 17 , suggesting shallow evolutionary trajectories and limited or absent adaptive divergence among local populations.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…One distinct characteristic of the species is its greater flight ability, presumably leading to frequent gene flows between populations. Fan et al previously reported that this species has low levels of genetic structure and relatively high gene flow 17 , suggesting shallow evolutionary trajectories and limited or absent adaptive divergence among local populations.…”
mentioning
confidence: 90%
“…Genome scans used in parallel with environmental data provide distinct clues for selective forces that act on molecular markers of adaptive relevance in the real landscape 17 and will complement and strengthen robustness of the final set of loci identified as potentially under selection 18 . It is now possible to implement such an approach relatively cheaply on a genome-wide scale.…”
mentioning
confidence: 99%
“…Genetic drift alone may act on insect populations, resulting in genetically distinct populations, due to reproductive isolation, or interruption of gene flow among regions [ 15 ]. Further, reproductive isolation is impacted by the population size, individual dispersal, geographic isolation, and local ecological adaptation [ 16 , 17 , 18 , 19 ]. Dispersal is a key factor in both population dynamics and genetic exchange [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insect populations may become genetically distinct because of reproductive isolation or lack of gene flow between different regions [12]. Further, reproductive isolation is influenced by several factors such as individual dispersal ability, ecological isolation, geographic barriers, and local adaptation after natural selection [13][14][15][16]. Dispersal is a key factor in population dynamics [17].…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, backcross hybrid between Drosophila buzzatii and Drosophila koepferae species was detected using AFLP [26]. AFLP was used to detect the impacts of human activities on the Bamboo Locust Ceracris kiangsu genetic structure in China [13] and the population dynamics of Hydropsyche orientalis and Stenopsyche marmorata in Japan [27].…”
Section: Introductionmentioning
confidence: 99%